A Comprehensive Review on Inclusive Education: Critical Approach to Supporting Children with Autism - Sachdeep Singh; Sangeeta Kakkar; Ashu Kumari (International Journal of Children, 2024)
A developmental illness that affects people to varied degrees over a range, autism spectrum disorder (ASD) is defined by difficulty with social interaction, communication, and repetitive activities. This study investigates useful methods for integrating ASD children into regular educational settings. The aim of inclusive education is to integrate students with autism spectrum disorder (ASD) into mainstream classroom environments. The review paper employed a systematic literature review approach, together with comparative policy analysis, and data analysis to detect patterns and gaps. The study examines earlier pertinent studies of the last five years on inclusive education for students with ASD. Working together, with parents, educators, and experts is essential to developing supportive learning environments. By cultivating an environment where differences are celebrated and individual strengths are recognized, we pave the way for a more inclusive and equitable society. Addressing these challenges requires a commitment from all stakeholders to invest in the necessary resources and policy changes that prioritize inclusive practices. To enhance the implementation of inclusive education, the study recommends modifying policies and behaviors. This guarantees that ASD kids get the assistance they require to thrive in the classroom and social situations. In order to better meet the varied needs of children with ASD, it also emphasizes the significance of individualized teaching methods, early intervention, and continuing professional development for educators. An educational culture that celebrates diversity and encourages equal chances for all students is fostered by a collaborative approach.
Keywords: Inclusive education; autism spectrum disorder; educational strategies; mainstream classrooms; social inclusion